How could someone who rewards me be wrong? Young children's preferences for and attributions of competence to inaccurate rewarding versus inaccurate non-rewarding interaction partners. - Barth, Maria. (2017)
Abstract: Preschool-aged children are adept at detecting another person's obvious inaccuracy or ineffectiveness. Do the social emotional characteristics of an agent influence children's preferences for an agent? Do these characteristics influence children's assessments of an agent's competence? Previous research shows that adults who have high self-esteem are more likely than those who have low self-esteem to view individuals who provide favorable feedback as more competent; the current study examines whether this phenomenon is also present in children. The current study also examines whether, in addition to endorsing the competence of agents, children follow, or reject, the lead of an inaccurate agent in their behavior, a nonverbal measure of children's endorsement of an agent's competence. In two experiments, I examined children's perception of agents who act in a both socially-emotionally positive manner and also inaccurate manner. Experiment 1, a cross-sectional study, found that a higher age predicts choosing the positive inaccurate agent as a favorite, and that children of all ages are more likely to follow the incorrect lead of a positive inaccurate agent than follow the lead of a negative one. Experiment 2 found replication of the effect in Experiment 1 that higher age predicts choosing the positive inaccurate puppet as the favorite. Neither Experiment 1 nor Experiment 2 found evidence for self-esteem as a predictor of any of these outcomes.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Psychology.; Advisor: Heather Urry.; Committee: Keith Maddox, Paul Muentener, and Carol Dweck.; Keywords: Psychology, Developmental psychology, and Social psychology.